2021
DOI: 10.1007/s00412-021-00753-0
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of pericentric HSATII RNA results in nuclear RNA accumulation, MeCP2 recruitment, and cell division defects

Abstract: Within the pericentric regions of human chromosomes reside large arrays of tandemly repeated satellite sequences. Expression of the human pericentric satellite HSATII is prevented by extensive heterochromatin silencing in normal cells, yet in many cancer cells, HSATII RNA is aberrantly expressed and accumulates in large nuclear foci in cis. Expression and aggregation of HSATII RNA in cancer cells is concomitant with recruitment of key chromatin regulatory proteins including methyl-CpG binding protein 2 (MeCP2)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…They found that lncRNAs from HSat2, but not from αSat, accumulated in visible foci and recruited MeCP2 in cis with the transgene. Furthermore, they found that ectopic satellite expression resulted in segregation defects [154]. These results suggest that the formation of nuclear stress bodies and chromosome instability phenotypes in cancer cells result directly from aberrant satellite transcription rather than some other property of cancer.…”
Section: Satellite Dna Transcription Can Occur In Cancerous Senescent...mentioning
confidence: 98%
See 1 more Smart Citation
“…They found that lncRNAs from HSat2, but not from αSat, accumulated in visible foci and recruited MeCP2 in cis with the transgene. Furthermore, they found that ectopic satellite expression resulted in segregation defects [154]. These results suggest that the formation of nuclear stress bodies and chromosome instability phenotypes in cancer cells result directly from aberrant satellite transcription rather than some other property of cancer.…”
Section: Satellite Dna Transcription Can Occur In Cancerous Senescent...mentioning
confidence: 98%
“…HSat2/3 lncRNAs play a role in recruiting splicing factors and other proteins such as MeCP2 to nuclear stress bodies [136,[150][151][152], and they are associated with mitotic segregation defects [153]. A recent study examined these phenomena further by stably expressing ectopic HSat2 lncRNAs from a transgene randomly integrated into a primary human fibroblast line [154]. They found that lncRNAs from HSat2, but not from αSat, accumulated in visible foci and recruited MeCP2 in cis with the transgene.…”
Section: Satellite Dna Transcription Can Occur In Cancerous Senescent...mentioning
confidence: 99%
“…When protein-coding genes are juxtaposed to pericentric heterochromatin due to genomic rearrangements, they undergo silencing in some somatic cells but not in others, a phenomenon called position-effect variegation (PEV) [ 219 , 220 , 221 ]. Human pericentric satellites are silenced in normal cells but are aberrantly expressed in many cancer cells, which coincides with the accumulation of methyl-CpG binding protein 2 at pericentromeres [ 222 , 223 ]. Pericentromeric satellites assemble highly condensed constitutive heterochromatin, which once established during development, remains permanently condensed during interphase.…”
Section: Satellite Chromatinmentioning
confidence: 99%
“…They found that lncRNAs from HSat2, but not from αSat, accumulated in visible foci and recruited MeCP2 in cis with the transgene. Furthermore, they found that ectopic satellite expression resulted in segregation defects (Landers et al 2021). These results suggest that the formation of nuclear stress bodies and chromosome instability phenotypes in cancer cells result directly from aberrant satellite transcription rather than some other property of cancer.…”
Section: Epigenomic and Functional Studies Of Hsat1-3mentioning
confidence: 98%
“…HSat2/3 lncRNAs play a role in recruiting splicing factors and other proteins such as MeCP2 to nuclear stress bodies (Aly et al 2019, Hall et al 2017, Ninomiya et al 2020, and they are associated with mitotic segregation defects (Giordano et al 2020). A recent study examined these phenomena further by stably expressing ectopic HSat2 lncRNAs from a transgene randomly integrated into a primary human fibroblast line (Landers et al 2021). They found that lncRNAs from HSat2, but not from αSat, accumulated in visible foci and recruited MeCP2 in cis with the transgene.…”
Section: Epigenomic and Functional Studies Of Hsat1-3mentioning
confidence: 99%